Promotion Mix Implementation in a Culinary MSME: A Case Study of Sarang Kepiting - Akmalia, Dina; Agustini, Prima Mulyasari (Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role as a main pillar of Indonesia’s economy; however, their sustainability increasingly depends on the ability of business actors to implement effective and adaptive marketing communication strategies amid intense competition. This study aims to analyze the application of the promotion mix in the marketing communication strategy of Sarang Kepiting, a seafood culinary MSME that has been operating since 1983 in North Jakarta. This research contributes novelty by examining the promotion mix in a long-established culinary MSME with a multi-generational customer base, emphasizing promotional practices that are contextual, relationship-oriented, and embedded within service interactions. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with the owner, employees, and customers, as well as observation and documentation. The findings indicate that Sarang Kepiting has implemented all elements of the promotion mix, advertising, sales promotion, public relations, personal selling, and direct marketing, although the implementation remains simple, situational, and not yet systematically structured. Personal selling emerges as the most dominant element in building customer loyalty. This study concludes that the application of the promotion mix contributes positively to brand awareness and business sustainability, and has the potential to enhance the competitiveness of culinary MSMEs if managed more consistently and integratively across all elements.